Back Cover: Electronic Materials: An Antiaromatic Propeller Made from the Four‐Fold Fusion of Tetraoxa[8]circulene and Perylene Diimides (Angew. Chem. Int. Ed. 48/2022). Issue 48 (18th November 2022) - Pedersen, Viktor B. R.; Pedersen, Stephan K.; Jin, Zexin; Kofod, Nicolaj; Laursen, Bo W.; Baryshnikov, Glib V.; Nuckolls, Colin; Pittelkow, Michael
Abstract : An antiaromatic molecular propeller acts as a strong electron acceptor, fluorophore, and dye in bulk heterojunction solar cells. In their Research Article (e202212293), Glib V. Baryshnikov, Colin Nuckolls, Michael Pittelkow, and co‐workers report how annulation of four perylene diimides to a tetraoxa[8]circulene gives a dynamic non‐planar π‐conjugated molecule with 32 aromatic rings surrounding a central planarized cycloctatetraene. The molecule accepts up to ten electrons, which induces a significant gain of aromaticity.